SOSIALISASI PENGGUNAAN ECOMMERCE DALAM PERKEMBANGAN BISNIS DI ERA DIGITAL - Niki Ratama; Munawaroh; Sri Mulyati (Abdi Jurnal Publikasi, 2022)
Information is a message addressed to the recipient or seeker of the message, or a collection of data or facts that have been processed and managed in such a way that it becomes something that is easy to understand and useful for the recipient. Of all aspects of life affected by the presence of the internet, the business sector is the sector most affected by the development of information technology and telecommunications and the fastest growing. Now emerging transactions using internet media that connect producers and consumers. Through e-commerce, all humans on earth have the same opportunities and opportunities to compete and succeed in doing business in cyberspace. With the rapid development of e-commerce around the world, online customer segmentation is attracting the attention of business people and academics. The development of online business in Indonesia cannot be separated from the ballooning of cellular and internet users in the last five years. On the other hand, the government continues to encourage cellular operators and internet providers to reduce all transaction fees charged to consumers. So that online business becomes the choice of modern entrepreneurs. E-commerce is usually carried out by business people through websites (sites). The widespread use of the website is closely related to its superiority in conveying information that is not limited by space and time. Through online shopping sites, shopping patterns in people's lives, especially people who are active in using the internet, are now experiencing significant changes. With the internet, consumers no longer need to go directly to the place of shopping but simply access the sites of online buying and selling providers. In addition, in making payment transactions the buyer can transfer funds to the seller. Not only direct transfers, in order to maintain the security of buyers, they can also use third parties or joint accounts provided by online buying and selling owners.